Professionalization of management in sports vis-a-vis the liability of management board members for the obligations of a sports club - KOSOWSKI, JAKUB (Baltic journal of health and physical activity, 2020)
Background: ‪The paper addresses one of the key issues relating to operations of sports entities, i.e. the liability for the obligations of the management board members. The aim is a comprehensive analysis of the legal basis of this subject, with abundant case-law in this matter taken into account. Material and methods: ‪The study is based on different criteria of the creation of the obligations of sports clubs, which entails a very high degree of complexity and multiplicity of legal rules relating to the problem in question. Taking these criteria into account, an analysis of the views presented by scholars in the field and the relevant case-law has been carried out. Practical problems in the application of the above regulations have also been identified. Results: The results of the research lead to the conclusion that, in the light of the applicable legal regulations, the transfer of liability for the obligations of a sports club to the members of the board entails significant difficulties, especially when public-law obligations are concerned. In view of the above, the potential directions of action from public institutions were presented herein. Conclusions: As part of the conclusions, several options for systemic solutions were put forward, as the current legislation and the established case law of administrative courts do not allow public institutions to effectively pursue the fulfilment of obligations. In view of the above, in the author’s opinion, it is necessary to amend the statutory provisions as put forward in the proposals de lege ferenda.